The electrochemically initiated reaction of sulfide with N,N-diethyl-p-phenylenediamine in dimethylformamide. Part II: Implications for sensing strategies - Giovanelli, D; Lawrence, N; Klymenko, O; Jiang, L; Jones, T; Compton, R (2003)
The electrochemically initiated reaction of p-phenylenediamines with sulfide in aqueous media is well documented. We now report the adaptation of this chemistry into nonaqueous media. This is critically appraised as a means of detecting sulfide. The electrochemically initiated reaction of N,N-diethyl-p-phenylenediamine with sulfide is shown at both macro- and platinum microdisk electrodes with quantitative detection of sulfide produced by means of the enhanced currents observed upon its addition. The linear detection range for sulfide is dependent on the concentration of N,N-diethyl-p-phenylenediamine present with a linear range from 28-3290 μM and a limit of detection of 22 μM achievable. This represents a large increase compared to that found previously in aqueous media and offers the prospect of more ready applications in high temperature systems.